Life Course Change Towards a Plant-Centered Diet and Incidence of Type 2 Diabetes: The Coronary Artery Risk Development in Young Adults (CARDIA) Study (OR33-03-19). (13th June 2019) - Choi, Yuni; Jacobs, David; Hirahatake, Kristin; Larson, Nicole; Odegaard, Andrew; Rana, Jamal; Shikany, James; Steffen, Lyn
Abstract: Objectives: There has been limited study of long-term change towards a plant-centered diet in relation to incident type 2 diabetes (T2DM). We examined this question in the Coronary Artery Risk Development in Young Adults (CARDIA) cohort. Methods: Analyses included 2717 participants in CARDIA, a US multicenter, community-based prospective cohort study, currently with 30 years of follow-up. Participants were free of diabetes through year 20, with follow-up for incident T2DM through year 30. Dietary intake at years 0 and 20 was assessed by interviewer-administered diet history; overall dietary quality was assessed using a hypothesis-driven index based on 46 food groups, the A Priori Diet Quality Score (APDQS). The APDQS has possible scores 0 to 132 and increasing score is largely led by consumption of nutritionally rich plant foods–fruits and vegetables and plant-derived fats (e.g., seeds, nut, vegetable oils) and proteins (e.g., avocado, legume, soy). Change in diet quality (year 20 – year 0) and its quintiles were calculated. Diagnosis of T2DM was based on self-reported use of antidiabetic medication treatment or lab tests (fasting glucose, 2-hour glucose, or glycated hemoglobin). In proportional hazards regression, covariates included sociodemographics, baseline APDQS, and time-varying energy intake, smoking, and physical activity. Results: Mean baseline age was 25.0 ± 3.6y, 43% were black, and 58% were women. During 10 years of follow-up after year 20, 206 cases of incident T2DM occurred. Mean year 0 APDQS was 64 ± 13 points and mean 20-year changes in APDQS was 7 ± 11. In multivariable-adjusted analysis, we found that the greatest increase in dietary quality over 20 years (median APDQS increased by 22 points) was associated with a 60% decrease in risk of T2DM as compared to a small decrease in diet quality (median APDQS decreased by 8 points); HRQ5 vs. Q1 : 0.40; 95% CI:0.24–0.67). For every 10-point increase in APDQS over 20 years, there was a 23% decrease in risk of T2DM (95% CI: 0.67–0.88, P-trend = 0.0009). The pattern of findings persisted within below median and within above median year 0 APDQS. Conclusions: Our finding suggests that young adults would benefit from improving diet quality by shifting toward a more plant-centered diet over time for the prevention of T2DM. Funding Sources: This research was funded by an NHLBI contract and the University of Minnesota Healthy Food, Healthy Lives Institute. Supporting Tables, Images and/or Graphs: